A Linguistic and Cultural Analysis of British Football Club Nicknames - Rababah, Luqman M.; Rababah, Mahmoud Ali; Haddad, Maram Teimah; Bani-Khair, Baker; Rababah, Khalid Ali; Wolor, Christian Wiradendi; Al-Thunebat, Sateh Abdullah; Kaddum, Mahmud (Forum for Linguistic Studies, 2024)
Nicknames are a byproduct of culture and are specific to the environment in which they are used and given. Onomasticology research has gained importance as linguists' interest in language and culture has grown. This study investigates the potential benefits and drawbacks of English football clubs’ (EFCs) nicknames as a communication tool. Specifically, it examines the nicknames of EFC players from the Premier League, Championship, League One, and League Two during the 2021–2022 season. The study sample includes all 92 EFCs in Britain, each of which has a nickname. These nicknames were categorized using a classification method and then compared. The analysis revealed statistically significant variations between the nicknames, with each conveying unique messages about language, society, or history while honoring the individuals associated with the term. The study highlights the importance of specific cultural elements in determining how EFCs acquire their nicknames. However, some nicknames tend to represent “culture-specific lexical concepts” that may be difficult for language learners to understand, especially those unfamiliar with English and British cultures. This exploration of nicknames aims to inspire further in-depth research at cross-cultural and intercultural levels to understand better how language reflects the significance of club nicknames.